AKLIMATISASI ANGGREK DENDROBIUM - Suyadi, Aman; Shofiyani, Anis (Sainteks, 2010)
This project shows how Dendrobium orchid acclimatization training can develop the skill of the orchid traders of Baturaden district on acclimatization technology, increase the income, and decrease the number of unemployment. The training was conducted towards 10 (ten) participants of PPAB group, and was continued by mentoring and monitoring until they acquired the skill of Dendrobium orchid acclimatization technology. The result proves that (1) the skill of Baturaden orchid traders on acclimatization technology increases, shown by the life percentage of seedling and compote plants that reaches 89.5%; (2) the average income of those traders increases in amount of Rp 4,094,167, or approximately Rp 409,417 per trader; (3) the number of unemployment decreases due to the increasing of employment number in amount of 5 (five) people, consisting of 3 (three) gardeners and 2 (two) florists. This sort of technique was shown to be an effective way of increasing Baturaden orchid traders’ skill on acclimatization technology and their income as well as the number of employment. Key words : Dendrobium orchid, acclimatization, skill